اتجاهات الطلب على المشتقات النفطية العربية - د. أحمد حسين الهيتي (PROSPECTIVE RESEARCHES, 2023)
The present research focuses on identifying demand directions of oil products through structuring consuming matrices of fuel resources in the Arab countries. In addition, tentative balances has been put to compare the production to consumption of oil products with the prediction of world demand tendency to reach the identification the needs to buildup investment the productive energies which satisfy demand and consumption.